Factors Associated with Puerperal Sepsis - Sabreena Abbas, Pireh, Tabinda Taqi, Farkhana Yasmen, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of factors associated with puerperal sepsis at tertiary care Hospital. Study design: Cross sectional study. Place and duration of study: Department of Obstetrics & Gynecology, Liaquat University Hospital Hyderabad from 1st August 2022 to 31st January 2023. Methodology: One hundred and fifty women of puerperal sepsis were enrolled. A detailed medical history, clinical examination and baseline equitable investigations including CBC, blood urea, creatinine and virology of all patients were done. The outcome variable i.e. cesarean section, postpartum hemorrhage, anemia, prolong labor, frequent vaginal examination and prolong rupture of membrane were noted. Results: The mean age was 27.5+7.5 years. Among factors associated with puerperal sepsis, most common factor observed was anemia 104 (69.5%) followed by PPH 89 (57.3%), frequent vaginal delivery 77 (51.3%), prolonged labor and prolonged rupture of membrane 74 (49.3%) each and c-section 32 (21.3%), cases. Conclusion: The factors associated with peripartum sepsis included mode of delivery, postpartum hemorrhage, prolonged labor, and anemia. Keywords: Puerperal sepsis, Mode of delivery, Risk factors